Approaches to measuring production performance enterprises in the oil and gas sector of the Russian Federation based on statistical reporting - M. D. Khabib; P. N. Maksimov (Вестник университета, 2022)
The article highlights approaches to calculating indicators characterising the production activities of oil and gas enterprises in the Russian Federation on the basis of the Federal State Statistics Service’s reports. The production activities structure’s heterogeneity has been noted. The issues of reassessing the importance of core and ancillary economic activities in the oil and gas sector are raised. The importance of assessing the intersectoral redistribution of value added is pointed out. Prospects for the performance assessment development of output, intermediate consumption and value added are highlighted an outlook by enterprise group analysis. The principles and criteria for assigning enterprises to the group are indicated. The output indicators of the largest companies in the oil and gas sector of the Russian Federation are considered. A methodology for step-by-step calculating the output, intermediate consumption and value added indicators for large enterprises is provided. The authors concluded that calculating the indicators of output, intermediate consumption and value added for the factor models construction is expediency.